Travel Restrictions in Siargao: An Intervention for the Island’s Long-Term Sustainability - Dellova, Rovena I.; Capadosa, Khrystal; Dangcalan, Janela A.; Descartin, Aliyah D.; Jatol, Rheem; Hernandez, Michelleana S.; Virrey, John Victor C. (Center for Risk Management & Sustainability and RSF Press, 2024)
An overwhelming influx of tourists to a destination can create massive pressure. Siargao, a tourism-first island known as